Effect of Vertical Shaft Propeller Turbine Blade Geometry on Generated Power - Rumagit, Paul M.; Siwi, Herroce; Maidangkay, Adrian; Pangow, Tammy T.V.; Tulung, Fransiscus J. (Indonesian Journal of Advanced Research, 2025)
Electricity availability is essential for improving quality of life in rural areas, particularly in remote regions of eastern Indonesia that lack access to the national power grid due to limited energy supply, transportation constraints, and weather conditions. To address this challenge, this study develops and tests a pico-hydro power system using a vertical-shaft propeller turbine capable of operating under low water flow conditions. The research was conducted in Tetey Village, North Minahasa Regency, utilizing irrigation canal water from rice fields. Direct experimental testing was applied to evaluate turbine performance under varying parameters, including blade type (plate and standard), blade angles of 30° and 40°, a water fall height of 50 cm, and a flow velocity of 0.68 m/s. The results show that the maximum turbine power of 200 W was achieved at 1800 rpm with a torque of 1.5 Nm using a standard four-blade turbine with a 30° blade angle and a water discharge of 0.065 m³/s. Overall, flow rate, fall height, blade type, and blade angle significantly affect turbine performance, demonstrating the potential of pico-hydro systems as an environmentally friendly electricity solution for rural areas with limited water flow.